IMPLEMENTASI IT SUPPORT OFFICER PDAM BANDARMASIH - Dwi Retnosari; Astrina Dwiyanti (INFO-TEKNIK, 2017)
One of the most important developments in information technology today is the need for the use of compatible, efficient, flexible and compatible data processing tools to solve existing problems in the enterprise. PDAM Bandarmasih is one company that utilizes technology for the company. From here comes the problem of hardware and software used must always be maintained, cared for, and observed its development.Implementation of IT Support Officer can manage PDAM management request. The request is in the form of repairing the problem computer, requesting the addition or replacement of spare parts, reffil catridge / tooner and distribution and others in the case of order request management and other complaints related to information technology in the company. This journal discusses the process of analysis, design in the implementation of IT Support Officer web-based and perform system testing.